2019
DOI: 10.1186/s12879-018-3640-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological description of a protracted cholera outbreak in Tonj East and Tonj North counties, former Warrap State, South Sudan, May-Oct 2017

Abstract: BackgroundOn 18th May 2017, State Ministry of Health of former Warrap State received a report from Tonj East County of an outbreak of acute watery diarrhoea and vomiting in Makuac payam. We conducted this investigation to confirm the causative organism and describe the epidemiology of the outbreak in order to support evidence-based control measures.MethodsWe defined a suspected case as a resident of Tonj East or Tonj North County with sudden onset of acute watery diarrhoea and vomiting between May 1 and Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…This may be explained by the fact that type two diabetes is common in old age people compare to young age people and the possibility of inheriting DM traits. Our findings are similar to the study conducted in Dar es salaam Tanzania, Kenya and Ethiopia 11 32 33 , but contrary to that of Nigeria 34 where no difference in the odds of DM was found.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This may be explained by the fact that type two diabetes is common in old age people compare to young age people and the possibility of inheriting DM traits. Our findings are similar to the study conducted in Dar es salaam Tanzania, Kenya and Ethiopia 11 32 33 , but contrary to that of Nigeria 34 where no difference in the odds of DM was found.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of DM among TB patients in this study is comparable with that reported in Dar es salaam Tanzania, (9.7%), Nigeria (9.4%), and a pooled prevalence of a meta-analysis study of SSA (9.0%). 11 , 16 , 25 However, the prevalence is lower compared to that reported in Pakistan (14.8%), India (13.9%) and Bangladesh (12.8) 26 28 Other studies have reported lower prevalence as compared to our study; Uganda (8.5%), Tanzania (4.5) Lusaka Zambia (2.3%), Mozambique (1%). 19 - 29 - 30 , 31 The possible explanations for the difference could be difference in study setting and screening method used in DM diagnosis, for example, in the study conducted in Pakistan 26 , both FBG and HBA1C were used for DM screening which is more effective as compared to the method used in the current study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…6 Oral cholera vaccines (OCVs) have been recommended in cholera-endemic settings and pre-emptively during outbreaks and complex emergencies. 7 This study reveals the challenges and gaps experienced in countries with insecurity regarding, prevention, early detection and effective response to public health threats. However, it also has limitations: Owing to surveillance challenges and insecurity in the area, several cases could have been missed at the beginning of the outbreak, which limits the reliability of our descriptive epidemiology.…”
Section: Discussionmentioning
confidence: 97%
“…Similar experiences have been documented in South Sudan and elsewhere. 53 Many countries that eventually declare outbreaks refer to the disease as "Acute Watery Diarrhea" or "AWD" for economic and political reasons; this creates distortions in response efforts.…”
Section: Why Are African Countries Unable To Timely Contain Cholera O...mentioning
confidence: 99%